HAp-functionalized zirconia surfaces via hybrid laser process for dental applications. (October 2018) - Carvalho, O.; Sousa, F.; Madeira, S.; Silva, F.S.; Miranda, G.
Graphical abstract: Highlights: Hybrid process showed to be an advantageous strategy to functionalize ZrO2 surfaces. HAp adhesion and retention were assessed testing different surface textures. HAp adhesion/degradation was evaluated for different laser powers and scan speeds. A new design with improved bioactivity is proposed for dental applications. Abstract: The development of new approaches to improve the implant integration and subsequently its long-term maintenance is an actual challenge. In this way and trying to mimic natural bone composition, HAp-functionalized zirconia surfaces were produced by means of hybrid laser technique combining additive (laser sintering) and subtractive (laser machining) processes. Nd:YAG laser-generated textures were created to improve mechanical interlocking of hydroxyapatite (HAp) powder and consequently enhance its adhesion to zirconia surface. Different laser parameters and also different approaches were tested to optimize the textured line-patterning of zirconia surface. The created microtextures were characterized by Scanning Electron Microscopy (SEM). Furthermore, textured zirconia surfaces were functionalized with HAp by means of CO2 laser. Different power and scan speed laser parameters were tested to promote HAp retention inside of line-patterning. The results showed that it is possible to design the textured surface by changing energy density and atmosphere. Furthermore, high amount of retained and sintered bioactive material was found when high laser power and low scan speed were performed.